The Reality of Social Interaction among Najran University Students and Ways to Enhance it in the University Learning Environment - Nimer , Ameen (Dirasat: Educational Sciences, 2021)
The study aims to identify the situation of social interaction among Najran University students from students' perspectives. The sample of the study (N=629 male and female students) was selected from the colleges of Humanities and Science. To achieve the objectives of the study, a questionnaire of (21) items was classified into three sections that measure aspects of interaction among students on one hand, and between students and faculty members on the other hand. The researcher utilized a descriptive analytical approach. The findings of the study revealed that mean score of social interaction among Najran University students from students' perspectives was (M=1.71) on a three-point Likert scale. The results also showed that there are statistically significant differences at the level of (α = 0.05) in the domain of specialization in favor of scientific specializations. The study recommends that the university should provide an environment that builds social relationships among its various parties, and that faculty members should have a primary role in providing opportunities that help create positive social interaction.